A Retrospective Study of Corrective Osteotomy for Cubitus Varus Deformity - Chand, Pankaj; Magar, Sushil Rana; Thapa, Bishnu Babu; Shah, Rajesh Pratap; Maharjan, Dipendra; Shrestha, B (Nepal Orthopaedic Association Journal, 2016)
INTRODUCTION: Cubitus varus deformity is the commonest complication of supracondylar fracture of humerus in children. Even though it does not cause any significant functional limitation, it is of cosmetic concern to the parents and children alike.METHODS: We carried out corrective osteotomies in 22 patients in 8 years from January 2005 to December 2013. The average age of the patients was 9 years, ranging from 6-14years. 14 were boys and 8 were girls. The average follow-up period was 34.6 months (range 29-73 months). Preoperative as well as postoperative clinical and radiological evaluation was done in all cases.RESULTS: 12 patients had cubitus varus deformity on the left elbow and 10 patients on the right side. The mean preoperative varus deformity was 21.8° (range 15°-30°) as compared to the mean carrying angle of the normal side which was 11.8° (range 8-14°). The mean postoperative carrying angle was 9.6° (range 7°-14°). The mean preoperative elbow range of motion was 126° (range 110°-130) and the mean postoperative elbow range of motion was 128° (range 112°-132°). One patient had postoperative superficial infection that was managed conservatively. One patient had lateral condylar prominence. A lateral closing wedge osteotomy (modified French osteotomy) was performed on all patients.CONCLUSION: Lateral closing wedge osteotomy is an effective surgery for correction of cubitus varus deformity in children.